Propriety and Impropriety in "Being and time" - Marínez Matías, Paloma (Pensamiento. Revista de Investigación e Información Filosófica, 2012)
The main aim of this essay is to reflect on the meaning of the concepts of propriety and impropriety (Eigentlichkeit-Uneigentlichkeit) in Martin Heidegger’s Being and time. By means of an expositionof some of the key moments of the existential analytic, we will try to show how in this work two diverse hermeneutic possibilities of the opposition «propriety-impropriety» coexist in permanent tension. Each possibility implies a decidedly different understanding of being-there (Dasein). While it is possibleto derive, either directly or indirectly, a moral evaluation from this dichotomy, the present investigationattempts to make evident those aspects of the text that seem to make such a derivation unfeasible and suggest instead an interpretation beyond an ethical perspective. Finally, we will take up the underlying problematic which could account for the ambivalence within Heidegger’s thinking during this time in relationto the polarity in question.
Keywords: Heidegger; Being and time; propriety-impropriety; ethics.